Believer's baptism sign of the New Covenant in Christ - Schreiner, Thomas R. (Nashville, TN Broadman and Holman, 2007)
Contents : Baptism in the Gospels -- Baptism in Luke-Acts -- Baptism in the Epistles : an initiation rite for believers -- Baptism and the relationship between the covenants -- Baptism in the Patristic writings -- "Confessor Baptism": the baptismal doctrine of the early Anabaptists -- Baptism and the logic of Reformed Paedobaptists -- Meredith Kline on Suzerainty, Circumcision and Baptism -- Baptism in the Stone-Campbell Restoration Movement -- Baptism in the context of the local church.
Keywords: Baptism (theology)